Association between triglyceride-glucose index and atrial fibrillation: A retrospective observational study - Chen, Shengnan; Mei, Qiao; Guo, Li; Yang, Xiaoli; Luo, Wenbin; Qu, Xuemei; Li, Xiaoping; Zhou, Bingqing; Chen, Ken; Zeng, Chunyu (Frontiers in Endocrinology, 2022)
Background: Insulin resistance is associated with atrial remodeling as well as atrial fibrillation (AF). However, there was limited evidence on the relationship of triglyceride-glucose index (TyG) index, a simple, valuable marker of insulin resistance, with AF. Thus, we aimed to investigate the association between TyG index and AF among hospitalized patients. Methods: A retrospective observational study was conducted in Daping Hospital, which included 356 hospitalized patients from the Department of Cardiology. Clinical and biochemical parameters were collected from electronic medical records and AF was diagnosed from electrocardiogram (ECG) findings. Results: We found that the TyG index was significantly higher in the AF group than in the group without AF. Multivariate logistic regression revealed that hypertension (OR = 1.756, 95%CI 1.135-2.717, P = 0.011) and TyG index (OR = 2.092, 95%CI 1.412-3.100, P＜0.001) were positively associated with AF. The analysis of the area under the ROC curve was performed and revealed that area under curve (AUC) of TyG index was 0.600 (95%CI, 0.542-0.659, P = 0.001), the optimal critical value was 8.35, the sensitivity was 65.4%, and the specificity was 52.0%. To assess the predictive value of TyG index for AF, the analysis of the area under the ROC curve was performed and revealed that area under curve (AUC) of TyG index was 0.600 (95%CI, 0.542-0.659, P = 0.001), the optimal critical value was 8.35, the sensitivity was 65.4%, and the specificity was 52.0%. Additional subgroup analyses of in diabetic and non-diabetic subjects were also performed and found the TyG index is increased in non-diabetic subjects with AF. Furthermore, a logistic regression analysis showed TyG index was associated with AF (OR = 3.065, 95% CI, 1.819-5.166, P＜0.001) in non-diabetic subjects. However, TyG index is not associated with AF in diabetic subjects. Conclusion: Elevated TyG index is an independent risk factor for AF among non-diabetic hospitalized patients.